Minimally Invasive Mitral Valve Repair with Intercostal Cryoablation: A Case Report - Luisa Humpfle; Andreas Böning; Bernd Niemann (The Thoracic & Cardiovascular Surgeon Reports)
Background Minimally invasive lateral thoracotomies may cause severe postoperative pain and discomfort. We describe an intraoperative intercostal cryo-neuronal pain block as one possibility for postoperative pain relief.